2002
DOI: 10.1038/sj.bjc.6600210
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of a complete pathological response after induction chemotherapy in operable breast cancer

Abstract: Only a few papers have been published concerning the incidence and outcome of patients with a pathological complete response after cytotoxic treatment in breast cancer. The purpose of this retrospective study was to assess the outcome of patients found to have a pathological complete response in both the breast and axillary lymph nodes after neoadjuvant chemotherapy for operable breast cancer. Our goal was also to determine whether the residual pathological size of the tumour in breast could be correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(94 citation statements)
references
References 22 publications
7
81
1
5
Order By: Relevance
“…Recently, this group has investigated pCR in both breast and axillary lymph nodes following neoadjuvant chemotherapy (Chollet et al, 2002). Retrospectively, they analysed 451 patients, of whom only 171 did not have clinically involved lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this group has investigated pCR in both breast and axillary lymph nodes following neoadjuvant chemotherapy (Chollet et al, 2002). Retrospectively, they analysed 451 patients, of whom only 171 did not have clinically involved lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed the incidence and outcome of patients with a pathological complete response (pCR) after neoadjuvant chemotherapy (Machiavelli et al, 1998;Kuerer et al, 1999;Chollet et al, 2002). Conversely, what is the role of residual disease on survival in patients with operable breast cancer after neoadjuvant chemotherapy?…”
Section: Discussionmentioning
confidence: 99%
“…For patients with neoadjuvant treatment, this approach enables the gathering of further information about the in vivo response to chemotherapy. Patients who have a complete nodal and breast pathological response enjoy a much better outcome than those who still have residual disease after therapy [46].…”
Section: Discussionmentioning
confidence: 99%